La génesis del título universitario de arqueología: Desde mi ángulo - Querol, M. ÁNGELES (Complutum, 2005)
This paper presents a personal view of the initiatives conducted since 1997 in order to demand an archaeological degree in the Second Cycle of Spanish university system. The Bologna Process for the implementation of the European Space for Higher Education means that the Spanish university system has to be reorganize and in that horizon we need an own degree in archaeology. There are solid arguments to defend the creation of a degree in archaeology: the complexity of modern discipline, the social demand of this humanistic studies, the necessity of having qualified staff for accomplishing legislation in archaeology, the urgency for sharing an archaeological degree as other European countries, and finally the existence of a qualified and numerous professorship to face the challenge.